2007
DOI: 10.4315/0362-028x-70.12.2717
|View full text |Cite
|
Sign up to set email alerts
|

Recirculating Immunomagnetic Separation and Optimal Enrichment Conditions for Enhanced Detection and Recovery of Low Levels of Escherichia coli O157:H7 from Fresh Leafy Produce and Surface Water

Abstract: The objective of this study was to develop a rapid, simple method for enhanced detection and isolation of low levels of Escherichia coli O157:H7 from leafy produce and surface water using recirculating immunomagnetic separation (RIMS) coupled with real-time PCR and a standard culture method. The optimal enrichment conditions for the method also were determined. Analysis of real-time PCR data (C(T) values) suggested that incubation of lettuce and spinach leaves rather than rinsates provides better enrichment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Separate duplicate rinse aliquots were processed exactly according to the FDA-BAM procedure, which confirmed that E. coli O157:H7 was absent from control leaves and present in spiked samples. Viable target counts obtained from FDA-BAM enrichments at the 7-h time point were 2 to 3 logs lower than those in SOP enrichments (2.4 ϫ 10 2 to 4.1 ϫ 10 3 CFU/ml), an observation that is consistent with previous reports (23,25). ECL signals and S/N ratios increased over baseline after 3 to 4 h of enrichment and continued to increase over the experimental time course (not shown).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Separate duplicate rinse aliquots were processed exactly according to the FDA-BAM procedure, which confirmed that E. coli O157:H7 was absent from control leaves and present in spiked samples. Viable target counts obtained from FDA-BAM enrichments at the 7-h time point were 2 to 3 logs lower than those in SOP enrichments (2.4 ϫ 10 2 to 4.1 ϫ 10 3 CFU/ml), an observation that is consistent with previous reports (23,25). ECL signals and S/N ratios increased over baseline after 3 to 4 h of enrichment and continued to increase over the experimental time course (not shown).…”
Section: Resultssupporting
confidence: 91%
“…Enrichment at 42°C without antibiotics served as the standard operating procedure (SOP) for all assays, except where direct analyses according to the FDA-BAM procedure are specified. The SOP conditions were chosen for short-term enrichments based on published reports indicating enhanced E. coli O157:H7 recovery at 42°C compared to that at 37°C (23,25). Aliquots of enrichment cultures were taken at all indicated time points (hourly), plated on CTSMAC, and processed for analysis using the ECL or IMS-cytometric bead array (IMS-CBA) assays.…”
Section: Methodsmentioning
confidence: 99%
“…[43,47,[60][61][62] New methods to make an earlier diagnostics of potential foodborne illness agents, such as E. coli O157 : H7 from fresh leafy produce and surface water, [63] can also help to avoid further consequences.…”
Section: Food Safety Issuesmentioning
confidence: 99%
“…In order to simulate normal environmental conditions, this study focused on the recovery of low organism seed levels from 40-liter surface water samples. Many studies have reported successful recovery of EHEC O157:H7 by the IMS/culture method in surface water, but these studies typically limited the analyses to sample volumes of ϳ100 ml of water and reported limits of detection ranging from 1 to 6 CFU/100 ml (10,11,18). One study in The Netherlands processed 1-liter samples and reported a limit of detection of 4 MPN/liter (7).…”
Section: Discussionmentioning
confidence: 99%